1996
DOI: 10.1063/1.472560
|View full text |Cite
|
Sign up to set email alerts
|

Energetically driven liquid–solid transitions in molecularly thin n-octane films

Abstract: In this paper we present findings from molecular dynamics simulations that investigated the changes induced in molecularly thin n-octane films, as a result of increasing solid-methylene unit energetic affinity. The solid surfaces were deprived of any topographical features and were modeled as atomically smooth 10-4 Lennard–Jones planes. We observed an abrupt transition in the structural features of the film at a critical value of the characteristic energy that quantified the affinity between solid surfaces and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 38 publications
4
24
1
Order By: Relevance
“…glassy dynamics. 36 Our observations of the flow of a polymer melt into a narrow slit with attracting walls are consistent with the dynamics of other strongly driven fluid systems.…”
Section: Resultssupporting
confidence: 86%
“…glassy dynamics. 36 Our observations of the flow of a polymer melt into a narrow slit with attracting walls are consistent with the dynamics of other strongly driven fluid systems.…”
Section: Resultssupporting
confidence: 86%
“…The influence of surface-molecule interactions on equilibrium and dynamical properties of confined molecules has been the subject of several computational investigations. [26][27][28][33][34][35] In these studies, an increased surface-polymer affinity is found to decrease molecular mobilities. Manias et al 28 have performed a moleculardynamics study of the motion of chain molecules in a thin film, which employed the same potentials that are used in the present work.…”
Section: ͑10͒mentioning
confidence: 92%
“…8,9 Understanding the formation kinetics and physical properties of these nanocomposites requires a molecular picture of the structure and dynamics of confined polymers. Laboratory studies employing the surface forces apparatus [20][21][22][23][24] and computational studies [25][26][27][28][29][30][31][32][33][34][35][36] have greatly increased our understanding of confined fluids. Confinement of a fluid on length scales comparable to the molecular size has been demonstrated to dramatically alter its structural and dynamical a͒ Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such forces were termed solvation forces because they are a consequence of the adsorption of solvent molecules to solid surfaces [711]. Exponentially decaying oscillatory solvation forces across confined liquids were first predicted by computer simulations and theory [711][712][713][714][715][716][717][718][719][720][721][722][723]. Experimental proof came a few years afterwards [724][725][726][727].…”
Section: Overviewmentioning
confidence: 99%